Editor’s note - Bonaldo, Alexandre Bragio; Xavier, Cláudia; Carvalho, Leonardo Sousa; Carvalho Filho, Fernando da Silva (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2024)
Editor’s note